2020
DOI: 10.1101/2020.06.09.141697
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RIL-StEp: epistasis analysis of recombinant inbred lines (RILs) reveals candidate interacting genes that control rice seed hull color

Abstract: Studying epistatic gene interactions is important in understanding genetic architecture of complex traits in organisms. However, due to an enormous number of gene combinations to be analyzed, detection of epistatic gene-gene interactions has been computationally demanding. Here, we show a simple approach RIL-StEp, specialized to Recombinant Inbred Lines (RILs), to study epistasis using single nucleotide polymorphisms (SNPs) information of the genome. We applied the method to reveal epistasis affecting rice see… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Varga et al [ 15 ] found that the component of melanin in oat bracts was homopolymer of p -coumaric acid, one of the key intermediates in the anthocyanin biosynthesis pathway with phenylalanine as a precursor, which was catalyzed by cinnamate 4-hydroxylase (C4H) [ 16 , 17 ]. In wild rice, black is considered to be the original color in the bracts controlled by two complementary genes— Bh4 ( black hull 4 ) and Phr1 ( phenol reaction 1 )—encoding a tyrosine transporter and a polyphenol oxidase, respectively, which are involved in melanin biosynthesis [ 18 , 19 , 20 , 21 ]. Notably, recent studies have shown that the formation of melanin in barley ( Hordeum vulgare L.) bracts occurred in chloroplasts [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Varga et al [ 15 ] found that the component of melanin in oat bracts was homopolymer of p -coumaric acid, one of the key intermediates in the anthocyanin biosynthesis pathway with phenylalanine as a precursor, which was catalyzed by cinnamate 4-hydroxylase (C4H) [ 16 , 17 ]. In wild rice, black is considered to be the original color in the bracts controlled by two complementary genes— Bh4 ( black hull 4 ) and Phr1 ( phenol reaction 1 )—encoding a tyrosine transporter and a polyphenol oxidase, respectively, which are involved in melanin biosynthesis [ 18 , 19 , 20 , 21 ]. Notably, recent studies have shown that the formation of melanin in barley ( Hordeum vulgare L.) bracts occurred in chloroplasts [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Genotyping of RILs by whole-genome resequencing To obtain the genotypes of the RILs, we performed whole-genome resequencing of the parents and 125 RILs using the Illumina DNA sequencing platform. Genotyping of RILs was carried out according to the method described by Sakai et al (2021).…”
Section: Pikps-1 Rnaimentioning
confidence: 99%